Caracterización hidrogeoquímico de aguas de producción de pozos petroleros del Lote 95 Petrotal – 2023 - Vásquez Flores, Iván Stefano (2024)
The present research aimed to characterize the hydrogeochemical properties of the produced waters from the 1XD, 2XD, 5H, and 14H wells in Lot 95 of PetroTal. A quantitative approach was used with a descriptive, comparative, and transversal methodological design, analyzing parameters such as pH, total dissolved solids (TDS), turbidity, hardness, and ionic composition. The data were collected during three periods in the year 2023. The results indicate that the wells are located in Vivian geological formations suitable for hydrocarbon accumulation, with depths ranging from 3,755 m to 5,137 m. The pH remained between 5.32 and 6.73, suggesting a slightly acidic character. Turbidity varied significantly, highlighting the decrease in well 1XD and fluctuations in well 5H due to geological and operational factors. The TDS in well 1XD reached levels between 74,279.88 mg/L and 114,060.58 mg/L, exceeding safe limits for reinjection, thereby increasing the risk of damage to the reservoir. An increase in water hardness was also observed, which may promote the formation of calcium sulfate scales. The chemical composition showed a predominance of sodium and chloride, emphasizing the salinity and corrosivity of the waters, concluding that there is a relationship between the water characteristics and the geological conditions of the area.